Internal security act 1960: has it outlived its purpose? / Ain-Nur ' Amiyerra Awod Abdullah, Kholyn Ruran Jonathan and Muhammad Taha Hamdan - Awod Abdullah, Ain-Nur ' Amiyerra; Jonathan, Kholyn Ruran; Hamdan, Muhammad Taha (2005)
This research shows that the Internal Security Act 1960 (ISA) has outlived its original purpose, which is to ensure public security from the threat of communism. Today, the country is no longer under the threat of communism. However, over the years, the ministerial power under the ISA has been abused as persons can be detained on suspicious basis. This research therefore justifies the need for an amendment in order for the ISA to fully serve in ensuring public security, including its other possible purpose such as in combating terrorism. The significance of this study is thus to highlight the need for a just judicial system under the ISA. The methodologies used in this research are analysis of statutes, in particular the Federal Constitution and the Internal Security Act 1960 itself, the Hansard and case laws. These analyses show that the ISA has outlived its original purpose and therefore is highly recommended to be amended or abolished.